Eksistensi Akad Dalam Kartu Kredit Syariah Hasanah Card Di Indonesia - Muhammad Isa; Siti Hajar Usman (Jurnal Hukum Ekonomi Syariah, 2019)
The rapid development of times, technology, and science cause various problems, likeproblems of the society needs in the economic such as need for something that make society tobe easy to running their daily, and to provide a sense of security, and sense of comfortable forthem. In order to meet the needs of modern society islamic bank is prosecuted to creat a variousproduct that comply with Islamic principles. Than BNI Syariah has published iB Hasanahcard product that function like credit card with Islamic principles.In order to know that a product in one syariah financial institution has according with syariahstandart, than nasional syariah board attend as a institution who have the rights to issue fatwaas a guidelines for syariah financial institution to creat their product with Islamicprinciples.This research is a qualitative study using normative law approaching, with fatwaDSN-MUI number 54 year 2006 about Syariah Card as a legal foundation. The results of thisstudy suggest that t implementation practice of iB hasanah card in BNI Syariah kendari branchoffice has suitable with fatwa DSN- MUI number 54 year 2006 about Syariah Card, in termsof akad, fees, limits and ta‟widh.